The Influence of Funding Decisions and Intellectual Capital on Firm Value in Indonesia’s Primary Consumer Goods Sector Listings - Nabila Evelyn Chandra; Vina Arnita (International Forum of Researchers and Lecturers, 2025)
This study aims to investigate the influence of funding decisions and intellectual capital on firm value in the primary consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The research population consists of 23 companies, from which a sample of 15 companies was determined using a purposive sampling technique based on specific selection criteria. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The results indicate that funding decisions, measured by the debt-to-equity ratio (DER), have a significant and positive effect on firm value. This finding suggests that companies that can effectively utilize debt to finance their operations and investments tend to generate sufficient profits, which contributes to an increase in market value. A higher DER often reflects the financing of profitable projects that can enhance shareholder wealth and attract investor confidence. On the other hand, intellectual capital, measured by value added capital employed (VACA), was found to have no significant impact on firm value. This result implies that the selected measurement indicator primarily emphasizes capital efficiency rather than directly capturing value creation activities driven by intangible assets. Consequently, intellectual capital in this form may not directly influence the company’s market valuation in the observed sector and period. The findings of this research highlight the critical role of funding decisions in improving firm value and the need for companies to carefully manage their capital structures. Moreover, business leaders should consider adopting broader or alternative approaches to measuring and utilizing intellectual capital to better capture its potential contribution to long-term value creation. By strategically balancing debt usage and optimizing intangible resources, firms in the consumer goods sector can enhance their competitiveness, market value, and sustainable growth.